The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2478/cszma-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution model for Buxbaumia viridis, identifying new areas of presumed distribution in the Czech Republic.

Abstract: There is a large number of organisms in nature that are hard to find in the field, and one of these is also a rare bryophyte species, Buxbaumia viridis, which can also only be found in a certain part of the year in the production of sporophytes. Using distribution models, however, it is possible to predict the locations which this species is likely to be present at and to focus the field research directly on such sites. Thanks to the presented model, we have succeeded in identifying areas within the Czech Repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…According to the results from the ensemble modeling, elevation, precipitation of the driest quarter, and mean temperature of the coldest quarter serve as the best indicators of Buxbaumia viridis occurrence. We can observe that the favored high-altitude areas typically correlate with the altitudinal range of mixed and spruce forests; hence there might be a dependence on habitat type, also supported by other studies [ 44 , 45 ]. Using maximum entropy modeling, Číhal [ 44 ] also argues that the found dependency of B. viridis to habitat type is most likely mostly connected to the species’ requirement for a sufficient quantity of decaying wood [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…According to the results from the ensemble modeling, elevation, precipitation of the driest quarter, and mean temperature of the coldest quarter serve as the best indicators of Buxbaumia viridis occurrence. We can observe that the favored high-altitude areas typically correlate with the altitudinal range of mixed and spruce forests; hence there might be a dependence on habitat type, also supported by other studies [ 44 , 45 ]. Using maximum entropy modeling, Číhal [ 44 ] also argues that the found dependency of B. viridis to habitat type is most likely mostly connected to the species’ requirement for a sufficient quantity of decaying wood [ 46 ].…”
Section: Discussionsupporting
confidence: 86%
“…We can observe that the favored high-altitude areas typically correlate with the altitudinal range of mixed and spruce forests; hence there might be a dependence on habitat type, also supported by other studies [ 44 , 45 ]. Using maximum entropy modeling, Číhal [ 44 ] also argues that the found dependency of B. viridis to habitat type is most likely mostly connected to the species’ requirement for a sufficient quantity of decaying wood [ 46 ]. However, when focusing on desiccation, Kropik [ 47 ] found that this variable outperforms decaying wood in terms of predicting power for explaining the occurrence of this moss in Austria.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, its sporophyte production, hence its finding and recording, depends on the increasingly variable climate, especially in the crucial part of the year i.e., unpredictable yearly local climate. So far, only a few studies have dealt with factors influencing its occurrence (e.g., [ 6 , 19 ]) or the identification of the potential (local) distribution of this significant species in Europe (e.g., [ 8 , 12 , 20 ]). Thus, in the research by Wiklund [ 19 ]., the number of occupied deadwood patches by B. viridis sporophyte was reduced by 73%, and the number of formed sporophytes even by 91%, during the dry year compared to the previous couple of years with higher precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, it was considered Endangered (EN) at the overall European level [ 11 ]. However, lately, it has been the subject of a number of various surveys and monitoring programs, that have resulted in many new records and increased its distribution knowledge, for example in Czechia [ 8 , 12 ], Poland [ 13 ], or Slovenia [ 14 ]. Due to the recent increase in the distribution data of the species, it was recently assessed as the Least Concern (LC) at the European continental level and so reported in the new European Red List (Hodgetts et al, 2019 a, b).…”
Section: Introductionmentioning
confidence: 99%